Otonomi daerah dan sengketa tanah. Pergeseran politik di bawah problem agraria - FAUZI, Noer (LAPERA Pustaka Utama, 2000)
Otonomi daerah dan sengketa tanah. Pergeseran politik di bawah problem agraria